KLICK syndrome: an overlooked form of congenital ichthyosis. - Mouhsine, Z.; Hali, F.; Allali, R.; Marnissi, F.; Chiheb, S. (European Journal of Pediatric Dermatology, 2024)
KLICK syndrome is a rare autosomal recessive inherited skin disorder linked to abnormal epidermal keratinization. It is characterized by transgrediens palmar plantar keratoderma, congenital ichthyosis and linear hyperkeratotic plaques. The case of a 21-year-old patient who presented with desquamation all over the skin and hyperkeratosis of the large folds since birth was reported.